Multidetector Computed Tomography-Based Microstructural Analysis Reveals Reduced Bone Mineral Content and Trabecular Bone Changes in the Lumbar Spine after Transarterial Chemoembolization Therapy for Hepatocellular Carcinoma - Takasu, Miyuki; Yamagami, Takuji; Nakamura, Yuko; Komoto, Daisuke; Kaichi, Yoko; Tani, Chihiro; Date, Shuji; Kiguchi, Masao; Awai, Kazuo (PloS one, 2014)
It is well recognized that therapeutic irradiation can result in bone damage. However, long-term bone toxicity associated with computed tomography (CT) performed during interventional angiography has received little attention. The purpose of this study was to determine the prevalence of osteoporosis and trabecular microstructural changes in patients after transarterial chemoembolization (TACE) for hepatocellular carcinoma therapy using an interventional-CT system. Spinal microarchitecture was examined by 64-detector CT in 81 patients who underwent TACE, 35 patients with chronic hepatitis, and 79 controls. For each patient, the volumetric CT dose index (CTDIv) during TACE (CTDIv (TACE)), the dose-length product (DLP) during TACE (DLP (TACE)), and CTDIv and DLP of routine dynamic CT scans (CTDIv (CT) and DLP (CT), respectively), were calculated as the sum since 2008. Using a three dimensional (3D) image analysis system, the tissue bone mineral density (tBMD) and trabecular parameters of the 12th thoracic vertebra were calculated. Using tBMD at a reported cutoff value of 68 mg/cm3, the prevalence of osteoporosis was assessed. The prevalence of osteoporosis was significantly greater in the TACE vs. the control group (39.6% vs. 18.2% for males, P<0.05 and 60.6% vs. 34.8% for females, P<0.01). Multivariate regression analysis demonstrated that sex, age, and CTDIv (CT) significantly affected the risk of osteoporosis. Of these indices, CTDIv (CT) had the highest area under the curve (AUC) (0.735). Correlation analyses of tBMD with cumulative radiation dose revealed weak correlations between tBMD and CTDIv (CT) (r2 = 0.194, P<0.001). The prevalence of osteoporosis was significantly higher in post TACE patients than in control subjects. The cumulative radiation dose related to routine dynamic CT studies was a significant contributor to the prevalence of osteoporosis.